Personal Selling to Reach Consumers (Case Study at PT. Teknologi Mudah Terhubung) - Bayuputra, Sultan Aulia; Mulyana, Dadan; Suherman, Maman (Eduvest - Journal of Universal Studies, 2025)
In the rapidly evolving business landscape, Indonesia has emerged as the sixth-largest country in terms of start-up growth. This surge in new enterprises necessitates that companies develop effective and efficient marketing and promotional strategies to remain competitive. Personal selling remains a crucial promotional tool, as demonstrated by PT. Teknologi Mudah Terhubung, which utilizes this method to market its products. This study aims to explore the stages of personal selling, the messaging strategies involved, the challenges faced during the process, and the rationale behind adopting the "Less Paper More Proper" concept in their promotional activities. Employing a qualitative research method with a case study approach and rooted in a constructivist paradigm, the research was conducted at PT. Teknologi Mudah Terhubung. The findings are anticipated to result in a refined personal selling model for the company, enhancing its consumer outreach. The study identifies the key stages of personal selling at PT. Teknologi Mudah Terhubung, which include prospecting, presentation and sales, handling objections, closing, and aftersales. The messaging strategies involve market research, message content, channels, and sources. Challenges include regulatory issues with potential corporate clients, public understanding of technology, and the certainty of agreements with prospective customers. The "Less Paper More Proper" concept is employed to emphasize environmental concerns and promote the sales of Leafcard products. This study contributes to a deeper understanding of effective personal selling strategies in the contemporary business environment.